Nation, empire and identity : monumental landscapes of the Duke of Wellington in nineteenth-century Ireland, Scotland and Wales - Stedman, Heather (Trinity College (Dublin, Ireland). Department of Geography, 2012)
This work comprises an analysis of the symbolic landscapes created by all the publicly placed, free-standing monuments dedicated to Sir Arthur Wellesley, the first Duke of Wellington, in Ireland, Scotland and Wales. Through reconstructing the nineteenth-century life histories of these monuments, it seeks to come to an understanding of their role as facets of the nineteenth-century cultural landscape, conveying particular conceptions of power and employing memory in a selective fashion to assist in the processes of identity formation.
Keywords: Natural Sciences, Ph.D.; Ph.D. Trinity College Dublin.